A cohesive zone model and scaling analysis for mixed-mode interfacial fracture. (15th December 2017) - Jain, Shruti; Na, Seung Ryul; Liechti, Kenneth M.; Bonnecaze, Roger T.
Abstract: A semi-analytical methodology is developed to study mixed-mode interface fracture that combines beam theory and cohesive zone interactions. The method is validated with predictions from a non-linear commercial finite element package and results in the literature. Compared to commercial finite element packages, the method is significantly faster ( > 1000X) and robustly converges. Scaling equations are extracted that predict load, crack length, damage zone length and mode-mix. These equations can be used to extract cohesive zone interactions from experimentally obtained load-displacement data.